Impacts of warming on outdoor worker well-being in the tropics and adaptation options - Masuda, Yuta; Parsons, Luke; Spector, June; Battisti, David; Castro, Brianna; Erbaugh, James; Game, Edward; Garg, Teevrat; Kalmus, Peter; Kroeger, Timm; Mishra, Vishmal; Shindell, Drew; et al. (Cell Press, 2024)
Over a billion outdoor workers live in the tropics, where nearly a fifth of all hours in the year are hot and humid enough to exceed recommended safety thresholds for workers conducting heavy labor. Reviews have focused on heat impacts on worker health, well-being, and productivity, but synthesis on how to increase resilience to heat for outdoor workers is lacking. Here we assess current and future heat exposure in the tropics and review four bodies of literature on heat impacts on workers. We also synthesize knowledge about mitigation and adaptation uncertainties as well as the actions that can be taken to strengthen worker resilience. We show that under an additional 1°C of warming, ∼800 million people in the tropics will live in areas where heavy work should be limited for over half of the hours in the year. Our review provides primary, secondary, and tertiary solutions that will inform policies and practices as well as research that is needed to bolster worker resilience and well-being.